Live monitoring system for ethernet passive optical network health using fiber Bragg grating - Rawi N.I.M.; Abdullah F.; Jamaludin M.Z.; Al-Mansoori M.H. (2023)
This paper presented a Live Monitoring System (LMS) for Ethernet Passive Optical Network (EPON) condition. Fiber Bragg Gratings (FBG) with different center frequencies is used as the monitoring devices. Different bit rates, of 2.5 Gbps and 10 Gbps are used as transmission speed. The performance of downstream signal with the monitoring signal propagating in the same fiber is observed. The simulation result shows that the performance of EPON system with 8 users is in acceptable range where transmission distance at bit error rate (BER) 10-9 is 47 km for 2.5 Gbps and 27 km for 10 Gbps system. 2010 IEEE.